THE PENGARUH TERAPI BERMAIN PUZZLE TERAHADAP TINGKAT KECEMASAN ANAK USIA PRA SEKOLAH AKIBAT HOSPITALISASI DI RUANG ZAMRUD SANTOSA HOSPITAL BANDUNG CENTRAL - mulhayati, nina; Mulhayati, Meilati; Yesayas, Oktavina (Alauddin Scientific Journal of Nursing, 2022)
Hospitalization is a process for reasons of emergency planning that requires the child to stay or be hospitalized. Hospitalization will have a significant negative effect on preschoolers. One of the children’s reactions to hospitalization is anxiety. The role of nurses in reducing anxiety is by providing puzzle play therapy. Puzzle games can help children focus more and reduce anxiety at preschool age. The purpose of this research was to determine the effect of puzzle play therapy on the anxiety level of preschool children in the Zamrud Ward, Santosa Bandung Central. This research is a research that uses a pre-experimental type. The design used is One-Group Pretest-Posttest. The sampling technique used in this study is Accidental Sampling with a sample of 48 people. Anxiety level with Face Anxiety Scale The results of data analysis using the marginal homogeneity test showed the effect of puzzle playing therapy on the anxiety level of preschool-aged children in the Zamrud Ward, Santosa Hospital Bandung Central with a p - value of 0.000. It is hoped that nurses can provide puzzle play therapy to reduce the age of preschool children during hospitalization.